Tyrosinase Inhibition and Photoprotection: Emerging Trends in Cosmetic Dermatology - Shivani Yadav,; Prateek Pandey, (Asian Journal of Pharmaceutical Research and Development, 2025)
Introduction: Hyperpigmentation and photodamage are common cosmetic concerns caused by overactive tyrosinase (the enzyme responsible for melanin synthesis) and prolonged exposure to ultraviolet (UV) radiation. Tyrosinase converts tyrosine to melanin, and its overactivity results in melasma, freckles, age spots, and post-inflammatory pigmentation. Concurrently, UVA and UVB rays generate reactive oxygen species (ROS), causing oxidative stress, DNA damage, inflammation, and accelerated skin aging.Objectives: This review aims to: (1) study the role of tyrosinase inhibition in controlling hyperpigmentation; (2) evaluate dual-action agents that provide both tyrosinase inhibition and photoprotection; and (3) assess safety, efficacy, and future potential of cosmetic formulations.Methodology: A detailed literature survey was conducted using peer-reviewed journals, scientific databases, and recent research publications (2010–2025), focusing on natural and synthetic tyrosinase inhibitors, their mechanisms of action, photoprotective properties, clinical evaluation, and safety.Results: Natural compounds such as flavonoids, phenolics, and plant extracts, along with synthetic derivatives like deoxyArbutin and thiosemicarbazones, demonstrate promising dual activity by inhibiting melanin synthesis while providing antioxidant and UV-protective effects. These agents improve skin tone, reduce pigmentation, and prevent oxidative damage, offering safer and multifunctional cosmetic solutions.Conclusion: Dual-function agents represent a modern and holistic approach in cosmetic dermatology. Future research should focus on stable formulations, enhanced skin penetration, long-term safety, and human-based clinical studies to ensure efficacy across diverse skin types.